Key access and utilization descriptors for barley genetic resources - Bioversity International; International Center for Agricultural Research in the Dry Areas (2009)
This list consists of an initial set of characterization and evaluation descriptors for barley utilization. This key set of strategic descriptors, together with passport data, will become the basis for the global accession-level information system being developed by the Bioversity-led project, Global Information on Germplasm Accessions (GIGA). It will facilitate access to and utilization of barley accessions held in genebanks and does not preclude the addition of further descriptors, should data subsequently become available.